Theoretical Investigation on the Electronic and Optical Properties of Poly(fluorenevinylene) Derivatives as Light-Emitting Materials - Thanisorn Yakhanthip; Nawee Kungwan; Jitrayut Jitonnom; Piched Anuragudom; Siriporn Jungsuttiwong; Supa Hannongbua (International Journal of Photoenergy)
Density functional theory (DFT) and time-dependent DFT (TDDFT) were employed to study ground-state properties, HOMO-LUMO gaps (ΔH-L), excitation energies (Eg), ionization potentials (IPs), and electron affinities (EA) for PFV-alt-PDONV and PFV-alt-PDIH-PPV having different alternating groups. Excited-state properties were investigated using configuration interaction singles (CISs) while fluorescence energies were calculated using TDDFT. The results show that PFV-alt-PDONV exhibits blue-shifted energies for both HOMO-LUMO gaps (ΔH-L) and excitation energies (Eg) compared with PFV-alt-PDIH-PPV. The predicted IP and EA clearly indicate that PFV-alt-PDIH-PPV has both easier hole creation and electron injection than that of PFV-alt-PDONV. The maximal absorption wavelengths of all polymers are strongly assigned to π→π∗ transition. The predicted radiative lifetimes of PFV-alt-PDONV and PFV-alt-PDIH-PPV for B3LYP/6-31G(d) are 0.36 and 0.61 ns, respectively, indicating that PFV-alt-PDIH-PPV should have a better performance for long-time emission than that of PFV-alt-PDONV.